Improving Psychological Interventions from the Perspective of Forensic Mental Health Service Users: A Meta-synthesis. Issue 2 (15th March 2022) - Cartwright, Jessica; Lawrence, Daniel; Hartwright, Christopher
ABSTRACT: Limited evidence exists for the effectiveness of psychological interventions that target the mental health needs of people who use forensic mental health services. Capturing service users' perspectives and experiences may provide information helpful to understanding why this is the case. It may also provide information that could help to improve the effectiveness of such interventions with this population. This paper aimed to address this and reviewed qualitative studies to identify the factors that are considered important to the effectiveness of interventions from the perspectives of service users. A review of the literature was conducted and eleven papers were identified as meeting the inclusion criteria. A meta-ethnography approach was used to synthesize the data. Six super-ordinate themes emerged which were synthesized into a hierarchy of treatment based on two main categories: " Treatment Foundations" and "Treatment Benefits." The findings suggested that addressing the Treatment Foundation factors such as enabling informed decision-making; developing trusting therapeutic relationships; and providing accessible materials whilst considering service user preferences can in turn result in service users benefitting from treatment in a number of ways. The findings have significant implications for future research, mental health service providers, clinicians and therapists, and for those who design therapeutic interventions.